SASTRA LISAN KOBA DALAM EKSPRESI PEKOBA (CIK ANI) DI PASIR PENGARAIAN KABUPATEN ROKAN HULU - Eko Wahyudi; Elmustian Elmustian; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is titled Koba Oral Literature in Pekoba (Cik Ani) Expression in the of Pasir Pengaraian Rokan Hulu District. The background of this research is that nowadays koba as an intangible cultural heritage is rarely performed again in the community and pekoba (koba Craftsman) has diminished its existence. The purpose of this study is to describe the expression of authors and authorship of pekoba (Cik Ani) in koba oral literature in Rokan Hulu District. This research is descriptive qualitative research that describes and describes the results of the research conducted. Based on the research, classified authors and authorship of Pekoba (Cik Ani) consisting of 8 aspects, 1) family background, 2) educational background, 3) profession, 4) role and social relations, 5) character, 6) creative process, 7) fellow profession, and 8) regeneration.Key Words: Oral literature, koba, author, authorship, pekoba